Potential Output and Output Gap in Central America, Panama and Dominican Republic - Johnson, Christian (IMF Working Papers; Working Paper, 2013)
Potential Output is a key factor for debt sustaintability analysis and for developing strategies for growth, but unfortunately it is an unobservable variable. Using three methodologies (production function, switching, and state-space), this paper computes potential output for CAPDR countries using annual data. Main findings are: i) CAPDR potential growth is about 4.4 percent while output gap volatility is about 1.9 percent; ii) The highest-potential growth country is Panama (6.5 percent) while the lowest-growth country is El Salvador (2.6 percent); iii) CAPDR business cycle is about eigth years.